G Gambaran Penggunaan Obat Antihipertensi Di RSUD Sultan Suriansyah Banjarmasin - Pratiwi, Wanda Nisa; Melviani, Melviani (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: The 2018 Riskesdas results the prevalence rate of hypertension in residents > 18 years based on national measurements of 34.11%. South Kalimantan Province has the highest prevalence of 44.13% (Ministry of Health of the Republic of Indonesia, 2018). Objective: The description uses antihypertensive drugs in South Kalimantan using samples from the Sultan Suriansyah General Hospital, Banjarmasin. Methods: This research was quantitative with an observational method with a cross-sectional design, data were collected retrospectively. This research took the form of patient medical record data at Sultan Suriansyah Hospital from January 2021 - March 2021. Results: There were 138 hypertensive patients were taking antihypertensive drugs including CCB (Calcium Channel Blockers) at 44.20%, Beta Blockers at 23.91%, Diuretics at 15.94%, ARB (Angiotensin Receptor Blockers) at 9.42% and ACEi (Angiotensin Converging Enzym Inhibitor) 6.52%. Conclusion: Based on the results the highest use of antihypertensive drugs was the CCB (Calcium Channel Blockers) group at 44.20% and the lowest was the ACEi group (Angiotensin Converting Enzym Inhibitor) at 6,52%.